EMERGING TRENDS IN TOURISM: A SUSTAINABLE DEVELOPMENT AND CONSERVATION OF GEOTOURISM, GEOPARK, AND GEO-HERITAGE IN INDIA - kumar, paramjeet (Revista de turism - studii și cercetări în turism, 2025)
Background of the study: An emerging sustainable tourism sector with global growth is Geotourism (GT). GT is very much beneficial in this context. It can conserve geosites and impart education to visitors, and at the same time, it can improve the local economy. Only little research has been done in this field though tourism promotion has a huge scope. Aim: Geological tourism, which has recently adopted natural and cultural geoheritage, has been understood to be more 'geographical'. This connection betwixt GT along with cultural heritage is largely unexplored. Yet, it signifies an opportunity to offer socio-cultural and economic benefits as GT supports cultural values and interests. Thus, this study examines India's emerging form of Sustainable Development (SD) and conservation of GT, geopark, and geoheritage. Methods: Data has been taken from 322 respondents from various geoparks in India by using a descriptive positivist approach and quantitative technique. Results: As per the findings, in response to visitors' perceptions, the government focuses on conserving geoheritage resources, promoting products, and collaborating with experts and community representatives for culturally sensitive development.